Intracellular Targets for a Phosphotyrosine Peptidomimetic include the Mitotic Kinesin, MCAK - Huang, Rong (2013)
SH2 domains are attractive targets for chemotherapeutic agents due to their involvement in the formation of protein-protein interactions critical to many signal transduction cascades. Little is known, however, about how synthetic SH2 domain ligands would influence the growth properties of tumor cells or with which intracellular proteins they would interact due to their highly charged nature and enzymatic lability. In this study, a prodrug delivery strategy was used to introduce an enzymatically stable, phosphotyrosine peptidomimetic into tumor cells. When tested in a human tumor cell panel, the prodrug exhibited a preference for inhibiting the growth of leukemia and lymphoma cells. In these cells, it was largely cytostatic and induced endoreduplication and the appearance of midbodies. Proteomic analyses identified multiple targets that included mitotic centromere-associated kinesin (MCAK). Molecular modeling studies suggested the ATP-binding site on MCAK as the likely site of drug interaction. Consistent with this, ATP inhibited the drug-MCAK interaction and the drug inhibited MCAK ATPase activity. Accordingly, the effects of the prodrug on the assembly of the mitotic spindle and alignment of chromosomes were consistent with the identification of MCAK as an important intracellular target.